DIGITAL PAYMENT MAXIMIZATION STRATEGY AS REGIONAL ECONOMIC RESILIENCE IN SURABAYA CITY MASS BUSS TRANSPORTATION - Panglipursari, Dwi Lesno; Arif, Mochamad Syaiful; Pujianto, Pujianto (LPPM STIE Muhammadiah Bandung, 2023)
The implementation of digital payment policies can be consistently applied and improve the security of digital transactions so as to avoid cyber-crime in the context of digital payments. The urgency of this study is that researchers observe that digital payment transactions on mass bus transportation in Surabaya City eliminate currency exchange. The problem-solving approach of this research uses a regional economic resilience perspective as the main paradigm in observing the phenomenon of digital payments in mass bus transportation in the city of Surabaya. The formulation of this research problem includes: 1) What is the dynamics of mass bus transportation payment transactions in the city of Surabaya? 2) What is the regional economic review on the digital payment for mass bus transportation in Surabaya? 3) What is the strategy to maximize digital payments on mass bus transportation in Surabaya? The stage of research methods to answer problems and achieve research objectives is the use of qualitative methods that are strengthened through the use of primary data and secondary data. The results of the study suggest that initiating payments should be less painful and more enjoyable than cash payments that put a higher mental price on goods. Empirical facts based on interviews show that payment using plastic waste makes it difficult for consumers who will use mass transportation. The economic acceleration has an impact on data collection that is facilitated through applications, the aspect of supervision increases in this context. The implementation of digital payment policies can be consistently applied and improve the security of digital transactions so as to avoid cyber-crime in the context of digital payments.